Health Education Practice in Libya; Professional Opinions - Abdulbaset A. Elfituri; Fathi M. Sherif (UiTM Publisher, 2009)
The aim of this study is to assess the perceptions of Libyan health professionals of their role in the provision of health education to the general public. It is also to identify barriers to effective health education and to suggest actions for a more effective role. A closedend questionnaire was distributed to 500 health professionals in five Libyan localities. Participants were requested to answer questions covering the responsibilities, importance and effectiveness of the existing role of health professionals in health education. Participants were also asked to indicate their perceptions of various barriers to the delivery of effective health education. A list of related suggested solutions for improving the practice was also presented. Nearly two thirds out of 500 health professionals responded to the questionnaire. A large majority perceived that they are responsible for providing health education and almost all (98.9%) considered this role very important or important. The effectiveness of their existing role was assessed differently. Participants perceived that lack of educational aids and materials and low priority for health education were the main barriers that should be overcome in order to improve services.